DESAIN PERANGKAT LUNAK OPEN SOURCE (LINUX) DI UNIVERSITAS SINGAPERBANGSA KARAWANG DENGAN METODA REMASTERING - Hendriadi, Ade Andri; Ridha, Azhari Ali; Heryana, Nono (Majalah Ilmiah SOLUSI, 2012)
Linux is open source software developed by various communities, so that linux has many variants and different distributions. The most popular linux distro is ubuntu. ubuntu is debian based operating system developed by Canonical Ltd. A Linux distribution, commonly called a "distro", is a project that aims to organize a collection of Linux-based software and facilitate the installation of a Linux operating system. Linux distributions are handled by individuals, teams, volunteer organizations and commercial entities. This thesis discusses the development of linux unsika distro with remastering techniques. Linux unsika developed from ubuntu linux. linux unsika development using structured stages, starting from concept development, requirements analysis, design of distribution, software package selection, interface design, and the remastering process. Linusk expected to used for academic purposes at the Universitas Singaperbangsa Karawang. Keywords— Distro, Linux, Remastering.